The Ojibwe Journals of Edmund F. Ely, 1833-1849. - Ely, Edmund F. (UNP - Nebraska, 2012)
Twenty-four-year-old Edmund F. Ely, a divinity student from Albany, New York, gave up his preparation for the ministry in 1833 to become a missionary and teacher among the Ojibwe of Lake Superior. During the next sixteen years, Ely lived, taught, and preached among the Ojibwe, keeping a journal of his day-to-day experiences as well as recording ethnographic information about the Ojibwe. From recording his frustrations over the Ojibwe's rejection of Christianity to describing hunting and fishing techniques he learned from his Ojibwe neighbors, Ely's unique and rich record provides unprecedente.